Prevalence of ischemic heart disease among urban population of Siliguri, West Bengal - Mandal Sukanta; Saha Joyti; Mandal Sankar; Bhattacharya Rudra; Chakraborty Manashi; Pal Partha (Wolters Kluwer Medknow Publications, 2009)
Objectives: To determine the prevalence of ischemic heart disease and the associated risk factors among the urban population of Siliguri. Materials and Methods: A cross-sectional survey of a random sample of the population aged ≥40 years old in the Municipal Corporation area of Siliguri. Study variables were age, sex, occupation, addiction, food habit, physical activity, body mass index, blood pressure, and electrocardiogram change. Results: Out of 250 individuals who took part in this study, 29 (11.6%) had ischemic heart disease (IHD) and 118 (47.2%) had hypertension. Males had a higher (13.5%) prevalence of IHD than females (9.4%). About 5% of the patients had asymptomatic IHD. IHD among the study population is significantly associated with hypertension and smoking.